2020
DOI: 10.3390/ijms21175974
|View full text |Cite
|
Sign up to set email alerts
|

Cachexia: Pathophysiology and Ghrelin Liposomes for Nose-to-Brain Delivery

Abstract: Cachexia, a severe multifactorial condition that is underestimated and unrecognized in patients, is characterized by continuous muscle mass loss that leads to progressive functional impairment, while nutritional support cannot completely reverse this clinical condition. There is a strong need for more effective and targeted therapies for cachexia patients. There is a need for drugs that act on cachexia as a distinct and treatable condition to prevent or reverse excess catabolism and inflammation. Due to ghreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 100 publications
(154 reference statements)
0
5
0
Order By: Relevance
“…Ghrelin (ghrl) is a 28-amino acid hormone produced primarily in the oxyntic mucosa of the stomach. This hormone binds to growth hormone secretagogue receptor the type 1a (GHS-R1a) in the hypothalamus and stimulates the release of growth hormones after catalyzed by ghrelin-O-acyltransferase (GOAT) [ 4 ]. The ghrelin GOAT system is responsible for regulating energy homeostasis, signaling the hypothalamus’ peripheral nutritional status inducing energy compensations; however, in the body, exogenous ghrelin is subject to very rapid degradation [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghrelin (ghrl) is a 28-amino acid hormone produced primarily in the oxyntic mucosa of the stomach. This hormone binds to growth hormone secretagogue receptor the type 1a (GHS-R1a) in the hypothalamus and stimulates the release of growth hormones after catalyzed by ghrelin-O-acyltransferase (GOAT) [ 4 ]. The ghrelin GOAT system is responsible for regulating energy homeostasis, signaling the hypothalamus’ peripheral nutritional status inducing energy compensations; however, in the body, exogenous ghrelin is subject to very rapid degradation [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The olfactory region of the nasal mucosa provides a connection between the nose and the brain, which can be used to more easily distribute drugs that act on the central nervous system [ 13 ]. In this context, the intranasal release of liposomes loaded with ghrelin to cross the blood-brain barrier and the release of the drug in the central nervous system can be a promising alternative to improve its bioavailability [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing the ability of ghrelin ligands across the BBB is being explored by researchers [42]. Barros et al found that ghrelin-loaded liposomes greatly improved the efficiency of delivering ghrelin and guaranteed the activity of released ghrelin [43]. In addition, it has been investigated that polymersomes conjugated with UAG are intended to be delivered to the brain across the BBB [38].…”
Section: Ghrelin and Apoptosismentioning
confidence: 99%
“…21 Despite these advantages, the IN route has some limitations including: short residence time of the administered formulation due to mucociliary clearance, drug degradation by enzymes in the nasal cavity that impair drug delivery to the brain and limit its bioavailability, and limited dosing in terms of volume (50-200 μL) administered in the nasal cavity. 23 Many recent literatures, less than five years, have been published on nose to brain delivery using nanoparticles, to overcome the IN limitations, such as nanoemulsion, 24 polymeric nanoparticles, 25 liposomes, 26 solid lipid nanoparticles (SLNs) 27 or nanostructured lipid carriers (NLCs), 28 which are effective nose-to-brain drug delivery systems that improve the nasal permeability and bioavailability of drugs for effective brain targeting by increasing drug solubility and permeation, reducing mucociliary clearance and enzymatic degradation. 29 In particular, formulations based on nanostructured lipid carriers (NLCs) are interesting candidates for nose to brain drug delivery without any modification to the drug molecule due to their rapid uptake by the brain, bioacceptability, biodegradability and safety.…”
Section: Introductionmentioning
confidence: 99%